Gc-Ms and Hplc Chromatographic Profile of Majority Volatile and Phenolic Compounds of Some Medicinal Plants From Romania - CIOTLĂUȘ, Irina; BALEA, Ana; POJAR-FENEȘAN, Maria; FILIP, Miuța Rafila; VLASSA, Mihaela (Studia Universitatis Babeș-Bolyai Chemia, 2024)
This study reports the identification of volatile organic compounds (VOCs) and the phenolic composition for these medicinal plants: lemon balm (Melissa officinalis), lavender (Lavandula angustifolia), and elderflower (Sambucus nigra). The HS-SPME-GC-MS hyphenated technique was used to investigate the volatiles from the three plants in fresh and dried forms. The essential oils were obtained by hydrodistillation technique, followed by GC-MS analysis. Additionally, HPLC-UV/VIS detection was used to identify the phenolic compounds of these plants. The majority compounds identified in the fresh, dried and oil of lemon balm were Z-beta-ocimene, citronellal, citronellol, b-caryophyllene, (E)-citral, (Z)-citral and geraniol respectively. The aerial part of lavender contains mainly linalool, linalyl acetate, beta-myrcene, trans-beta-ocimene, lavandulyl acetate and caryophyllene. The most compounds identified in the fresh flowers of elderflower were linalool, cis-beta-ocimene, linalool oxide (II) pyran, cis-3-hexenyl isovalerate, while in the dry flowers the majority compounds were linalool oxide (II) pyran, cis-3-hexenyl isovalerate and hexenyl tiglate. The essential oil was rich in n-hexadecanoic acid, linoleic acid, and heneicosane. Majority phenolic compounds identified in the analysed species were vanillic, sinapic, ferulic, and p-coumaric acids, while the predominant flavonoids were rutin, quercetin and epicatechin. The profile of VOCs represents an indicator in the valorisation of medicinal plants.